Protection of People Living Conflict A Case Study in Yemen - Yordan Gunawan; Aisah Nur; Fauziah Nauri Qisty; Mohammad Hazyar Arumbinang (Unnes Law Journal, 2021)
The Yemen war is a continuous conflict that first occurred in 2015. The war, known as the Yemen Civil War, involves two factions: Abdrabbuh Mansur Hadi leading the Yemen government, and the armed Houthi movement, along with their supporters and allies. Both claim to be the official government of Yemen. Iran-aligned Houthi rebels, who have controlled large parts of northern Yemen since 2014, have continued to carry out cross-border incursions into Saudi Arabia and are pressing for an offensive to seize Yemen's gas-rich Marib region. Already more than 100,000 people have died in Yemen's civil war, most of them civilians, because too many people have died in the civil war, so there is a need for legal protection. The purpose of this study is to find out how the protection of the people who are in conflict countries, especially the civil war in Yemen, is according to the perspective of international law. This study used a normative legal research method with a statute approach and a case approach to be easier to examine what is being studied, namely how to protect people living in conflicted countries from the perspective of international law. The results of this study indicate whether there is already legal protection for people who are in a conflicted country and how it is protected according to the perspective of international law.